Sleep Respiratory Disorders in Children and Adolescents with Cystic Fibrosis and Primary Ciliary Dyskinesia - Maria Papale; Sara Manti; Santiago Presti; Federico Mollica; Giuseppe F. Parisi; Salvatore Leonardi (MDPI AG, 2023)
Cystic fibrosis (CF) and primary ciliary dyskinesia (PCD) are genetic respiratory diseases featured by chronic upper and lower airway inflammation and infection, mainly due to impaired mucociliary clearance due to genetic mutations. Sleep is crucial to healthy children's normal physical and psychological development and has an important value in chronic respiratory diseases. Impaired sleep quality, such as sleep deprivation or insufficient sleep during the night, and sleep respiratory disorders (SRDs) are common in 5% to 30% of the general population. Sleep disruption leads to attention deficits, daytime sleepiness, fatigue and mood disorders and correlates to a worsened quality of life. Furthermore, sleep respiratory disorders (SRSs) are under-recognized comorbidities in CF and PCD patients. SRSs include a spectrum of symptoms ranging from primary snoring through upper airway resistance to obstructive sleep apnea (OSA), nocturnal hypoventilation and hypoxemia occurring in people with moderate to severe lung disease and damaging the disease-related outcomes and quality of life. Effective screening during sleep with polysomnography is very important for the timely initiation of efficacious treatments and to prevent worsened respiratory, metabolic and cardiovascular outcomes. However, the impact of SRDs on health and quality of life is still underinvestigated.